2020
DOI: 10.21608/jfds.2021.60281.1014
|View full text |Cite
|
Sign up to set email alerts
|

Texture, Sensory Attributes and Antioxidant Activity of Spreadable Processed Cheese with Adding Date Seed Powder

Abstract: Effect of supplementation with roasted date seed powder (DSP)on the texture and sensory properties of spreadable processed cheese was carried out. Four different formulas of processed cheese were prepared (F-C, F-1, F-5, and F-10) with added 0, 1, 5, and 10 % of roasted DSP.Results revealed that the DSP is of higher total phenolic (TPC, 38.3 mg GAE/g) and flavonoid (TFC, 33.4 mg QE/g) contents, and antioxidant activity (AOA, 83.9%).Adding DSP resulted in significant differences (P ˂ 0.05) in total solids and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Replacement with date pit powder at 5% elicited the highest ratings on sensory acceptability and overall acceptability. Similarly, in the case of spreadable cheese, the addition of date pit powder at levels of up to 10% was found to be acceptable in relation to antioxidant activity and sensory properties (Darwish et al, 2020). Overall, the acceptable concentration range for the addition of date pits is lower in the case of dairy products as compared to other food products.…”
Section: Date Pits In Dairy Productsmentioning
confidence: 86%
See 1 more Smart Citation
“…Replacement with date pit powder at 5% elicited the highest ratings on sensory acceptability and overall acceptability. Similarly, in the case of spreadable cheese, the addition of date pit powder at levels of up to 10% was found to be acceptable in relation to antioxidant activity and sensory properties (Darwish et al, 2020). Overall, the acceptable concentration range for the addition of date pits is lower in the case of dairy products as compared to other food products.…”
Section: Date Pits In Dairy Productsmentioning
confidence: 86%
“…This application in fortification has subsequently progressed to their use in the enhancement of other functionalities beyond traditional nutritional enrichment. Examples of the functionalities of date pits include their use to enhance consumers' perceptions of a product's physical and textural properties (Bouaziz F. et al, 2020;Darwish et al, 2020;Alqattan et al, 2021), to increase shelf life (Najafi et al, 2016;Ghasrehamidi and Daneshi, 2019;Sayas-Barberá et al, 2020;Abushal et al, 2021), as a fat replacer (Ammar et al, 2014;Essa and Elsebaie, 2018;Alqattan et al, 2021), and as a natural meat tenderizer (i.e., to enhance sensory juiciness, texture, and taste; Nor et al, 2018). Recently, date pits have been used in more innovative ways, such as in the formulation of biodegradable edible coatings that can enhance shelf life, and in the production of low-fat products via reduction of oil uptake during the frying process.…”
Section: Applications Of Date Pits In Foods Food Productsmentioning
confidence: 99%
“…Likewise, the authors reported a proportional increase in mineral content (Na, K, Fe, and Zn) compared to the control samples and a higher content of total polyphenols and flavonoids. This work also showed that the meltability and oil separation index decreased over storage time when date seed powder was added and that the samples obtained good sensory acceptability [ 84 ]. Alqattan et al [ 85 ] evaluated the use of this date by-product as a promising and novel fat replacer and fiber source in processed cheese block types.…”
Section: Application Of Date Fruits Products and Co-products In Foodsmentioning
confidence: 99%
“…Various applications of date seeds in food products , 5, and 10%Fortied cheese with 1% and 5% seed powder showed signicant differences in total solids and ber contents, with favorable sensory acceptance Darwish et al (2020)240 reduction in total volatile nitrogen, TBAR level, and aerobic bacterial counts compared to the control, extending the shelf life and preventing the growth of pathogenic strains, such as Salmonella and Campylobacter. Essa and Elsebaie (2018)142 proposed another application of date seed powder as a fat replacement agent in meat products.…”
mentioning
confidence: 99%